Physical Activity Policy for Older Adults in the Northwest Territories, Canada: Gaps and Opportunities for Gains - Brooks-Cleator, Lauren A.; Giles, Audrey R. (ARCTIC, 2016)
In the Northwest Territories (NWT), Canada, the population of older adults is increasing, and this population reports much poorer health than other age cohorts. Given the number of benefits that physical activity (PA) can have for older adults, we analyzed policies concerning older adults and PA of both the NWT government and non-governmental organizations in the health, recreation, and sports sectors. Our findings indicate that although the majority of the organizations had no PA policies specific to older adults or Aboriginal older adults, some organizations completed all five stages of the policy cycle (agenda setting, policy formulation, decision making, implementation, and evaluation). Our analysis suggests that PA for older adults is not on the agenda for many organizations in the NWT and that often the policy process does not continue past the decision-making stage. To address the need for connections between all stages of the policy cycle, we suggest that organizations collaborate across multiple sectors and with older adults to develop a territory-wide, age-friendly rural and remote community strategy that is applicable to the NWT. Prioritizing age-friendly communities would, in turn, facilitate appropriate PA opportunities for older adults in the NWT and thus contribute to a healthier aging population. Dans les Territoires du Nord-Ouest (T.N.-O.), au Canada, la population de personnes âgées augmente, et la santé de ce segment de population est bien inférieure à celle des autres segments. Étant donné les bienfaits que peut comporter l’activité physique (AP) chez les personnes âgées, nous avons analysé les politiques concernant les personnes âgées et l’AP au sein des organismes gouvernementaux et non gouvernementaux des Territoires du Nord-Ouest en matière de santé, de loisirs et de sports. Nos constatations indiquent que même si la majorité des organismes n’étaient pas dotés de politiques d’AP visant particulièrement les personnes âgées ou les Autochtones âgés, certains organismes avaient déjà fait ...